Developing Crime Safety Model and Tool Kit on Prevention Responses Remedial (P2R) Towards Property and Violent Crimes - Ishak, Noor Azniza; Kamsani, Siti Rozaina; Mustaffa, Jamaludin; Ibrahim, Nabisah (UUM, 2021)
This study examines an approach to property crime prevention and violence strategies that can be used by enforcement agencies as well as the community in ensuring that the crime rate in our country decreases. In addition, the recommendations of the crime safety tool kit are also listed in educating the public on the prevention and response that needs to be done during or before the occurrence of crime as one of the crime prevention processes. This study is quantitative using the questionnaire survey method. The sample of this study is 300 respondents consisting of communities in the northern areas involving the states of Kedah, Perlis and Penang. Based on the results of the study, aspects of strategies that can be used in dealing with property crime and violence nowadays The PDRM needs to work with the community and other agencies to fight crime. Regarding the action that needs to be taken in the event of a criminal incident, the community must first identify the guests who come to the house before allowing guests to enter. And the response that will be made if it is found that a crime has occurred to oneself or another person, the main thing that needs to be done at that time is to win oneself during the incident. Therefore, it can be discussed as a whole that these findings are very useful to the community as a precautionary measure. To ensure the crime of property and violence can be reduced, the emphasis on strategies and tool kits is very important to ensure a quality and prosperous life for the present and future generations.